A force platform free gait analysis - Maeda, T.; Ishizuka, T.; Yamaji, S.; Ohgi, Y. (Proceedings, 2018)
Using multiple cameras with force platforms is a classical and popular method for gait analysis. However; it is difficult to measure natural walking; because the subjects have to adjust their steps to place on the force platform. This study proposes two rigid body linked segment models to estimate the joint force and ground reaction force without force platform. In order to validate the accuracy of the models; the authors compared their kinetic parameters with those of classical model. The results showed that the proposed models could estimate the ground reaction force and the joint force with high accuracy (less than 10% in the third quartile on all axes). In addition; using the center of pressure from force platform could also estimate the joint torque with high accuracy. These results suggest that we can analyze the gait without force platform; if the center of pressure is provided in the future.